(untitled) (Journal on studies and research of academic knowledge, 2021)
The city of Encarnación is surrounded by sub-reservoirs with good-purification capacity, but there are occasional contamination points such as the municipal landfill area that can affect this capacity. The objective of this work is to calculate the Quiteria sub-reservoir kinetic constants of oxygenation and deoxygenation of the water. With data from the biochemical oxygen demand, dissolved oxygen is obtained at three points and it is calculated by the 5-day BOD test at 20 degrees centigrade, then the value of k1 and k2 is obtained by the Streeter-Phelps formula. The biochemical oxygen demand values increased as the sampling point approached the leachate discharge area from the municipal landfill. The result obtained in terms of kinetic constant k1 and k2 is peculiar because, on the one hand, the river has a good capacity to incorporate air from the atmosphere and on the other, there is a high rate of deoxygenation, which indicates contamination.